2020
DOI: 10.1017/s0029665120000038
|View full text |Cite
|
Sign up to set email alerts
|

The effect of quantity and quality of dietary fat intake on subcutaneous white adipose tissue inflammatory responses

Abstract: The global prevalence of obesity and obesity-associated cardiometabolic diseases is a significant public health burden. Chronic low-grade inflammation in metabolic tissues such as white adipose tissue (WAT) is linked to obesity and may play a role in disease progression. The overconsumption of dietary fat has been suggested to modulate the WAT inflammatory environment. It is also recognised that fats varying in degree of fatty acid saturation may elicit differential WAT inflammatory responses. This information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 123 publications
(212 reference statements)
0
6
0
Order By: Relevance
“…28,29 Furthermore, EPA and DHA can bind to receptors such as peroxisome proliferator activated receptors (PPARs) 30 to regulate the expression of genes associated with lipid accumulation in WAT, 31,32 and to G-protein coupled receptor (GPR)-120 to regulate inflammation and insulin sensitivity. 33 Therefore, EPA and DHA have the potential to reduce inflammation in adipose tissue but investigation of this in human scWAT is limited, as highlighted in a recent review by Dewhurst-Trigg et al 34 Obesity is accompanied by several pathophysiological changes in adipose tissue, but the mechanisms behind these have not been well elucidated with reports predominantly focussing on circulating markers of inflammation. In addition, the metabolic health of individuals living with obesity is often overlooked when trying to understand the link between obesity and adipose tissue inflammation which can also be said for assessing the effects of LC n-3 PUFAs.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…28,29 Furthermore, EPA and DHA can bind to receptors such as peroxisome proliferator activated receptors (PPARs) 30 to regulate the expression of genes associated with lipid accumulation in WAT, 31,32 and to G-protein coupled receptor (GPR)-120 to regulate inflammation and insulin sensitivity. 33 Therefore, EPA and DHA have the potential to reduce inflammation in adipose tissue but investigation of this in human scWAT is limited, as highlighted in a recent review by Dewhurst-Trigg et al 34 Obesity is accompanied by several pathophysiological changes in adipose tissue, but the mechanisms behind these have not been well elucidated with reports predominantly focussing on circulating markers of inflammation. In addition, the metabolic health of individuals living with obesity is often overlooked when trying to understand the link between obesity and adipose tissue inflammation which can also be said for assessing the effects of LC n-3 PUFAs.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…During the feeding/fasting cycle, in physiological conditions, an intermittent, non-specific, low-grade inflammatory response occurs at the level of “metabolic tissues” (adipose, muscle, and liver tissue), which results in a transient increase in some inflammatory proteins/cytokines in the serum. This increment reaches its maximum peak during the absorption phase (post-prandial) and then gradually decreases in about 2 h, when the nutrients have been distributed, metabolized, and/or accumulated in the respective cellular sites [ 32 ]. The inflammatory response is amplified in overeating conditions (hyperlipidic diet, excess of saturated fats and simple carbohydrates, and low intake of fiber, vitamins, and antioxidant compounds), in obesity, and in diabetes—when the metabolic overload generates a “traffic jam” of the physiological metabolic pathways, progressive recruitment and activation of immune-competent cells, such as macrophages, mast cells, and T lymphocytes, occurs [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…An examination of data from the National Health and Nutrition Examination Survey (NHANES 99-00) found that levels of SFAs in serum phospholipids of male civil servant workers (40–69 years) positively correlated with some inflammatory markers, such as HS-CRP (high sensitivity C-reactive protein) and fibrinogen; by contrast, phospholipid PUFA levels were inversely associated with HS-CRP [ 32 , 36 ]. It has been recently shown in a C57BL/6 male mice model that consuming a high-fat diet, enriched with SFAs, induces especially adipose IL-1β inflammation and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also recently reported that a 7-day period of lipid oversupply plays a role in the development of vascular inflammation and atherosclerosis (8). However, there is very little information on the initiation of inflammatory signaling pathways within WAT in response to acute overnutrition (9). Previous high-fat overfeeding studies (3-to 56-days) have examined gene expression of targets involved in WAT inflammatory pathways, such as pro-inflammatory cytokines (IL-6, TNF-α and MCP-1), macrophage markers (cluster of differentiation (CD)68, CD11c and CD40), and components of the NF-κB pathway (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%